Which global tennis rating better measures player skill? Evidence from the 2022 USTA Junior National Championships - Mayew, R. L.; Mayew, W. J. (The Sport Journal, 2023)
Assessing relative player skill is important in many aspects of tennis. In 2008, the Universal Tennis Rating (UTR) was introduced as a global tennis player skill rating that put all players, regardless of gender, age or geographic location, on a common scale. The International Tennis Federation (ITF) recently launched a competitor rating called the World Tennis Number (WTN). The purpose of this paper is to provide evidence on which rating is a superior measure of player skill. We assume better skilled players are more likely to win tennis matches and examine whether UTR or WTN ratings better predict head-to-head match success using 1,532 matches played by 870 participants at the 2022 United States Tennis Association (USTA) Junior National Championships. We observe classification accuracy of 73.9% and 70.4% for UTR and WTN ratings, respectively. Both classification accuracy levels are statistically greater than chance and approximate the accuracy level observed for bookmakers at the professional level. UTR and WTN rating classification accuracy does not statistically differ between ratings in the sample overall, by age division, by gender, by match format, or by the magnitude of player rating differences. We conclude that UTR and WTN ratings are equivalent measures of player skill based upon their ability to predict match outcomes. These findings provide initial empirical evidence important to tennis organizations making rating adoption decisions, tennis coaches seeking play parity, tournament directors seeding players and college coaches screening potential recruits. We provide mapping functions between UTR and WTN ratings for situations where players have one rating but not the other.